Insights on drug and gene delivery systems in liver fibrosis - Kunj Vyas; Mayur M Patel (Elsevier, 2023)
Complications of the liver are amongst the world's worst diseases. Liver fibrosis is the first stage of liver problems, while cirrhosis is the last stage, which can lead to death. The creation of effective anti-fibrotic drug delivery methods appears critical due to the liver's metabolic capacity for drugs and the presence of insurmountable physiological impediments in the way of targeting. Recent breakthroughs in anti-fibrotic agents have substantially assisted in fibrosis; nevertheless, the working mechanism of anti-fibrotic medications is not fully understood, and there is a need to design delivery systems that are well-understood and can aid in cirrhosis. Nanotechnology-based delivery systems are regarded to be effective but they have not been adequately researched for liver delivery. As a result, the capability of nanoparticles in hepatic delivery was explored. Another approach is targeted drug delivery, which can considerably improve efficacy if delivery systems are designed to target hepatic stellate cells (HSCs). We have addressed numerous delivery strategies that target HSCs, which can eventually aid in fibrosis. Recently genetics have proved to be useful, and methods for delivering genetic material to the target place have also been investigated where different techniques are depicted. To summarize, this review paper sheds light on the most recent breakthroughs in drug and gene-based nano and targeted delivery systems that have lately shown useful for the treatment of liver fibrosis and cirrhosis.